Identifying Root Cause and Derived Effects in Causal Relationships - Bae, Juhee; Helldin, Tove; Riveiro, Maria (Human Interface and the Management of Information: Information, Knowledge and Interaction Design, 2017)
This paper focuses on identifying factors that influence the process of finding a root cause and a derived effect in causal node-link graphs with associated strength and significance depictions. We discuss in detail the factors that seem to be involved in identifying a global cause and effect based on the analysis of the results of an online user study with 44 participants, who used both sequential and non-sequential graph layouts. In summary, the results show that participants show geodesic-path tendencies when selecting causes and derived effects, and that context matters, i.e., participant’s own beliefs, experiences and knowledge might influence graph interpretation.